Nuevos registros para avifauna uruguaya - Arballo, Eduardo (1990)
The distribution of rare or seldom observed bird species in Uruguay is extended. The country represents a southern distribution limit for some species, and others are threatened. The observations given here are the result of many surveys to several points of the country.